Parâmetros comportamentais e neuroquímicos em modelo experimental de deficiência grave de tiamina - Leticia de Souza Resende (2012)
Although, the thiamine deficiency (TD) causes lesions and/or dysfunctions in several brain regions, the thalamus and the mammillary bodies are the regions more frequently affected. Thiamine deficiency can lead to behavioral impairments, including memory, learning and motor deficits in both humans and animals models. However, the precise mechanisms underlying these pathological changes are still unknown. To approach this question, we performed four independent experiments whose objectives were to evaluate the effects of TD on: protein expression profiles in the thalamus and the correlation between spatial cognitive performance and the levels of thalamic proteins (Experiment 1); hippocampal synapsin I and phosphorylated synapsin I levels and the rats performance during spatial task (Experiment 2); ama-amminobutiric acid (GABA) and glutamate levels in various brain regions and motor aspects (Experiment 3); in vivo GABA, glutamate and acetylcholine release and the rats performace during spontaneous alternation task (Experiment 4). The TD treatment was similar in all experiments and consisted of treating the animals with thiamine deficient diet associated with daily pyrithiamine (inhibitor of the enzyme that produces the active phosphorylated form of thiamine-TTP) injections. Controls animals received thiamine-deficient chow associated to daily injections of thiamine (Experiments 2 and 4) or standard chow combined with saline injections (Experiments 1 and 3). In the Experiment 1 behavioral aspects were assessed using Morris Water Maze (MWM) test and protein expression of thalamus was analyzed using two-dimensional electrophoresis gel. Seven protein spots were found to be differentially regulated as a function of TD: three increased and four decreased (p < 0.05). Regression analysis between the concentrations of each one of these seven proteins and latencies to find the platform in the MWM revealed a significant correlation with four speficic proteins (p<0.05). The data suggest that the process of neurodegeneration induced by severe TD involves alterations (both up and down regulation) in specific proteins within the thalamus. In the Experiment 2 we used the spontaneous alternation task to evaluate working memory. Western blot was performed to analize hippocampal synapsin I and phosphorylated synapsin I levels. Positive correlations between spontaneous alternation behavior and hippocampal levels of synapsin I or phosphorylated synapsin I were found only in control rats. However, spontaneous alternation performance was impaired in PTD rats (p=0.01) and was accompanied by a significant reduction (30%) in phosphorylated synapsin I (p=0.02). These data suggest thiamine deficiency degrades the link between spatial behavior and hippocampal synapsin I and phosphorylated synapsin I protein levels. In the Experiment 3 motor coordination and balance in rodents were evaluated using rotarod and beam balance tasks and excitatory and inhibitory neurotransmitters concentrations in the hippocampus were assessed using HPLC. There was no effect of thiamine deficiency on the assessed motor aspects. The DT reduced the levels of glutamate in the cerebellum (p=0.02) and the levels of GABA in the hippocampus (p=0.01) and cerebellum (p=0.01). On the other hand, the glutamate and GABA levels in prefrontal cortex and striatum were not affected by TD. Thus, thiamine and/or its derivatives seem to play a specific role in the maintenance of levels of GABA and glutamate in some regions of the CNS. Because this effect is region-specific, it might not be related to the role of this vitamin as a coenzyme in energy metabolism. That is, it seems to involve a different mechanism of action. In the Experiment 4, Using HPLC, the GABA, glutamate and acetylcholine hippcampal levels were measured in vivo before, during and after spontaneous alternation task. There were significant effects of thiamine deficiency on the glutamate (p= 0.03) and acetylcholine (p=0.01) release over the phases. In addition, positive correlation between spontaneous alternation behavior and the amount of acetylcholine released during the performance of the maze task was found. There was a tendency (p=0.07) to correlation between the amounts of acetylcholine and glutamate released. These data show that the hippocampus cholinergic and glutamatergic system are involved in the spatial learning and memory events. In conclusion, the present data show thalamic protein changes and hippocampal neurochemical dysfunction associated with behavioral changes in animal model of severe thiamine deficiency, contributing to clarify part of the mechanisms underlying this disorder.